Identification of Single Nucleotide Polymorphism on Growth Hormone Gene in Aceh Cattle - E M Sari; R R Noor; C Sumantri; M Yunus; Han J L; . Muladno (Faculty of Animal Science, Bogor Agricultural University, 2013)
This research was aimed to identify the changes of nucleotide (Single Nucleotide Polymorphism) growth hormone gene in the population of Aceh cattle. There were 44 samples of DNA sequenced, and a few samples from Gen Bank (M57764). Based on the analysis using MEGA program, it was identified one new mutation on exon five on 2230 bp in which C nucleotide turned into T nucleotide, and this was called Silent Mutation (Leusine-Leusine/ CTC-CTT). The frequency of Single Nucleotide Polymorphism (SNP) genotype on 2230 bp (C/T) was CC (0.36), TT (0.14) and CT (0.50). The genotype TT was not possessed by Aceh cattle from Saree, but possessed by those from Banda Aceh and Indrapuri. Chi-square test showed not significant differences in allele frequencies for three population. The frequency of genotype SNP on 2291 bp (A/C) was AC (0.11) and CC (0.89). The frequency of allele C was higher than allele A and T.